COVID-19 in the Americas: Who's Looking After Refugees and Migrants?. Issue 1 (29th June 2020) - Brito, Maximo O.
Several characteristics of refugee and migrant populations make them susceptible to acquire COVID-19. To fully understand the impact of COVID-19 on refugees and migrants in the Americas, it is important to consider the broader geopolitical context and appreciate the differences among migratory groups. There are three migrant groups in the Americas that are particularly susceptible to COVID-19: Central American migrants at the northern Mexico border, Venezuelans within South America, and Haitians in the Dominican Republic. Refugees and displaced migrants are the world's collective responsibility, and thus, it would be imprudent to displace their care to resource constrained developing nations.